2012
DOI: 10.1111/obes.12003
|View full text |Cite
|
Sign up to set email alerts
|

A Canonical Correlation Approach for Selecting the Number of Dynamic Factors

Abstract: In this article, we propose a selection procedure that allows us to consistently estimate the number of dynamic factors in a dynamic factor model. The procedure is based on a canonical correlation analysis of the static factors which has the advantage of being invariant to a rescaling of the factors. Monte Carlo simulations suggest that the proposed selection rule outperforms existing ones, in particular, if the contribution of the common factors to the overall variance is moderate or low. The new selection pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 29 publications
0
28
0
3
Order By: Relevance
“…As in the appendix of Breitung and Pigorsch (2013) it can be shown that as N → ∞ and T → ∞ the linear combination G r,t (or G s,t ) converges in probability to HG t , where H is some regular m 0 × m 0 matrix. Hence, G r,t yields a consistent estimator of the space spanned by G t .…”
Section: The Cca Estimatormentioning
confidence: 91%
“…As in the appendix of Breitung and Pigorsch (2013) it can be shown that as N → ∞ and T → ∞ the linear combination G r,t (or G s,t ) converges in probability to HG t , where H is some regular m 0 × m 0 matrix. Hence, G r,t yields a consistent estimator of the space spanned by G t .…”
Section: The Cca Estimatormentioning
confidence: 91%
“…It is important to note that the procedures for determining the number of factors considered in this paper are designed for what is known in the literature as static factors. Alternatively, several factor determination procedures have been proposed in the context of dynamic factors; see, for example Amengual and Watson (2007); Hallin and Liska (2007); Bai and Ng (2007); Jacobs and Otter (2008) and Breitung and Pigorsch (2013). The difference between static and dynamic factors is described by, for example, Bai and Ng (2008).…”
Section: Introductionmentioning
confidence: 99%
“…The idea of the test is that a r×r semipositive definite matrix of rank q has q nonzero eigenvalues and that a sequence of test statistics on the ordered eigenvalues of the VAR's residual covariance matrix converges to zero if the considered rank is greater than the true one. Related approaches for selecting the number of dynamic factors in a DFM have been developed that we do not consider here but refer the reader to Barhoumi et al (2013) or Breitung and Pigorsch (2013) who give an overview.…”
Section: Methodsmentioning
confidence: 99%